2021
DOI: 10.25076/vpl.43.04
|View full text |Cite
|
Sign up to set email alerts
|

The possibility of using digital educational platforms in teaching English: theoretical aspect

Abstract: P h e n o m e n o no ff em a leso lida rit y inm o de m we b-spa ce . A ktua l 'n y e рr о Ы е т у l in gvistiki i l in gvodidaktiki in ostr a n n ogo j a zy ka del ovogo i p r of ession a l 'n ogo obshhen ija . Sbor n ik ma ter ia l ov I X M ezhdun a r odn ojn a uchn ojkonf er en cii. V 2-h cha stja h. ,(р. 32).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Flexible environment is the first aspect of a successful flipped learning organisation. The essence of this pillar is to offer students a great opportunity to flexibly rearrange the learning space according to individuals' preferences (Zainuudin & Halii, 2016;Nwosisi et al, 2016;Petrosyan & Grishechko, 2021). Demirel (2016) found that this flexibility creates a stress-free environment for both students and teachers and conclude that learners are not placed in traditional learning environments (such as lecture theatres), but rather they are allowed to individually adjust the environment according to the task in hand.…”
Section: The Four Pillars Of Flipped Learning: F-l-i-pmentioning
confidence: 99%
“…Flexible environment is the first aspect of a successful flipped learning organisation. The essence of this pillar is to offer students a great opportunity to flexibly rearrange the learning space according to individuals' preferences (Zainuudin & Halii, 2016;Nwosisi et al, 2016;Petrosyan & Grishechko, 2021). Demirel (2016) found that this flexibility creates a stress-free environment for both students and teachers and conclude that learners are not placed in traditional learning environments (such as lecture theatres), but rather they are allowed to individually adjust the environment according to the task in hand.…”
Section: The Four Pillars Of Flipped Learning: F-l-i-pmentioning
confidence: 99%
“…The purely mnemonic approach to a foreign language has long been shown to be inadequate, and although it is generally considered outdated, it unfortunately tends to persist when dealing with specialised languages. In order to overcome this trend, to break down the emotional filter and to achieve better and lasting learning results, teachers today have at their disposal, thanks to new media, devices and platforms (Petrosyan & Grishechko, 2021). Three of them seem particularly relevant to us and fruitful to be applied to the learning process of foreign languages in an integrated way: podcasts, TV series, and the literary text (which use has to be reconsidered on the basis of the new pedagogical theories).…”
Section: Problem Statementmentioning
confidence: 99%